Molecular Modification of Polysaccharides and Resulting Bioactivities. Issue 2 (16th September 2015) - Li, Shijie; Xiong, Qingping; Lai, Xiaoping; Li, Xia; Wan, Mianjie; Zhang, Jingnian; Yan, Yajuan; Cao, Man; Lu, Lun; Guan, Jiemin; Zhang, Danyan; Lin, Ying
Abstract: Polysaccharides are ideal natural resources for supplements and pharmaceuticals that have received more and more attention over the years. Natural polysaccharides have been shown to have fewer side effects, but because of their inherently physicochemical properties, their bioactivities were difficult to compare with those of synthetic drugs. Thus, researchers have modified the structures and properties of natural polysaccharides based on structure–activity relationships and have obtained better functionally improved polysaccharides. This review focuses on the major modification methods of polysaccharides, and discusses the effect of molecular modification on their physicochemical properties and bioactivities. Molecular modification methods mainly include chemical, physical, and biological changes. Chemical modification is the most widely used method; it can significantly increase the water solubility and bioactivities of polysaccharides by grafting onto other groups. Physical and biological modifications only change the molecular weight of a polysaccharide, and thereby change its physicochemical properties and bioactivities. Most of the molecular modifications bring about an increase in the antioxidant activity of polysaccharides, and among these, sulfated and acetylated modifications are very common. Furthermore, phosphorylation modification is the most common application to increase antitumor activity, and modified polysaccharides have been shown to have anti‐HIV activity as the result of sulfated modification.